A comparative study between the still births and full term normal deliveries based on the clinical history of mother - Sharma, Preksha; Chauhan, Sangita; Sharma, Shreya; Pahal, Parul (International Journal of Research in Medical Sciences, 2017)
Background: To study the impact of duration of pregnancy, obstetrical history of mother and age of the mother on foetal outcome in still birth and full term normal deliveries. Methods: After taking due permission from the ethical committee the study was conducted in the S.M.S. Medical College and attached group of hospitals. Results: Following parameters were recorded: (1) duration of pregnancy (in weeks): it was found that females reporting with still births have significantly lowered weeks of gestation; (2) obstetrical history: it was found that both groups were well comparable without any significant difference neither in gravidity nor in parity; (3): age of the mother: there was no significant (p>0.05) difference found in mean age of females of both the groups. Conclusions: Knowledge about the various factors leading to still birth is important so that that maximum attention could be paid on these causative factors so as to improve the outcome.